2020
DOI: 10.3892/ol.2020.11918
|View full text |Cite
|
Sign up to set email alerts
|

Erastin triggers autophagic death of breast cancer cells by increasing intracellular iron levels

Abstract: Erastin is a small molecular compound that induces ferroptosis by binding to voltage-dependent anion-selective channel protein (VDAC)2, VDAC3 and solute carrier family 7 member 5 inhibiting the cystine/glutamate antiporter. However, to the best of our knowledge, the mechanism of erastin-induced breast cancer cell death remains unclear. In present study aimed to explore the underlying mechanisms of the antitumor effects of erastin on breast cancer cells. Cellular viability was assessed using an MTT assay, a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Under conditions of both silencing their expression and lowering iron levels, erastin-induced cell death was not observed. This would suggest an involvement of both autophagy and ferroptosis in cancer cell death [ 47 ]. Thus, one can suggest either a two-way action of ferroptosis activators (which would induce autophagy at the same time) or a feedback linkage between ferroptosis and autophagy (initiated by ferroptosis).…”
Section: Implication Of Autophagy Process In Ferroptosis (Autophagmentioning
confidence: 99%
“…Under conditions of both silencing their expression and lowering iron levels, erastin-induced cell death was not observed. This would suggest an involvement of both autophagy and ferroptosis in cancer cell death [ 47 ]. Thus, one can suggest either a two-way action of ferroptosis activators (which would induce autophagy at the same time) or a feedback linkage between ferroptosis and autophagy (initiated by ferroptosis).…”
Section: Implication Of Autophagy Process In Ferroptosis (Autophagmentioning
confidence: 99%
“…Erastin is a compound that has a strong inhibitory effect on cancers that express the RAS gene, and it can mediate ferroptosis (7). Therefore, developing strategies that can improve the content, solubility and potency of erastin is of great significance for cancer treatment (55)(56)(57). Nanoparticle-induced ferroptosis has also been demonstrated in xenotransplantation studies (58).…”
Section: Tumor Neoantigens and Ferroptosismentioning
confidence: 99%
“…Studies have reported that the voltage-dependent anion channel (VDAC) 2 (VDAC2)/VDAC 3 pathway controls the transmembrane flow of adenosine diphosphate (ADP), phosphatidylinositol (PI), and adenosine triphosphate (ATP) on the mitochondrial outer membrane, and that tubulin can inhibit mitochondrial metabolism by blocking the VDAC2/ VDAC3 pathway, promoting aerobic glycolysis which is the main energy source for tumor cells. Erastin, on the other hand, can induce ferroptosis by inhibiting cystine/ glutamate antiporters by binding to VDAC2, VDAC3, and SLC7A5 (28). Additionally, in a U.S study it was found that the long-chain fatty acyl-CoA synthetase family member 4 (ACSL4), which is related to lipid metabolism, is one of the key proteins in ferroptosis (29).…”
Section: Other Mechanismsmentioning
confidence: 99%